SERVICE QUALITY AND CUSTOMER SATISFACTION ISSUES IN FRONT OFFICE BUSINESSES - Alobaidi, Muthanna (International Journal of Psychosocial Rehabilitation, 2020)
-This study is aimed to explore customer satisfaction of the Crystal Grand Hotel Ishtar hotel toward its front office services quality to assist Crystal Grand Hotel Ishtar hoteliers in formulating customized operations and strategies which will enhance their ability to perform the promised service to guests. A survey questionnaire was conducted and an equation of multiple regressions was used. Five hotel service quality dimensions were identified and four of them were important influential factors in determining guests’ overall satisfaction levels toward front office services as well as hotel services.